Orientia beyond fever and rash (Unusual presentations of scrub typhus) - Rajanna, Avinash Hanbe; Rajoli, Swetha (Asian Journal of Medical Sciences, 2021)
Scrub typhus is a zoonotic disease caused by an obligate intracellular gram-negative bacterium of the family Rickettsiaceae called Orientia tsutsugamushi. We are reporting three cases: Case 1:- A 42 year old male, farmer who presented with fever, rash and pandigital gangrene. Case 2:- A 52 year old female positive for scrub typhus treated came with c/o bilateral lower limb weakness which gradually progressed to upper limb, diagnosed to be AIDP, Case 3:- A 32 year old male presented with fever, maculopapular rash and leukocytoclastic vasculitis in first week of illness proved by biopsy. All three cases were positive for OXK (Weil Felix). Scrub typhus can present with unusual clinical features and complication during the course of illness and cases are reported for its varied presentations.